2007
DOI: 10.1038/nn1922
|View full text |Cite
|
Sign up to set email alerts
|

RECK modulates Notch signaling during cortical neurogenesis by regulating ADAM10 activity

Abstract: We report that during cortical development in the mouse embryo, reversion-inducing cysteine-rich protein with Kazal motifs (RECK) critically regulates Notch signaling by antagonizing the ectodomain shedding of Notch ligands, which is mediated by a disintegrin and metalloproteinase domain 10 (ADAM10). In the embryonic brain, RECK is specifically expressed in Nestin-positive neural precursor cells (NPCs). Reck-deficient NPCs undergo precocious differentiation that is associated with downregulated Nestin expressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
166
0
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 136 publications
(175 citation statements)
references
References 49 publications
6
166
0
3
Order By: Relevance
“…Notably, similar defects characterize also the cortex of embryos deficient in RECK (reversion-inducing cysteine-rich protein with Kazal motifs), a membrane protein localized to cortical precursor cells, which is thought to inhibit ADAM10 sheddase activity but with Notch ligands as substrates 40 .…”
Section: Discussionmentioning
confidence: 98%
“…Notably, similar defects characterize also the cortex of embryos deficient in RECK (reversion-inducing cysteine-rich protein with Kazal motifs), a membrane protein localized to cortical precursor cells, which is thought to inhibit ADAM10 sheddase activity but with Notch ligands as substrates 40 .…”
Section: Discussionmentioning
confidence: 98%
“…Recent papers also point to a link between EMT and cancer stem cells (Mani et al, 2008;Hill et al, 2009;Polyak and Weinberg, 2009). Reck has been implicated in angiogenesis (Oh et al, 2001), directional cell migration (Morioka et al, 2009) and suppression of neuronal differentiation (Muraguchi et al, 2007). Thus, the roles of RECK in hypoxia response, EMT and cancer stem cells are interesting subjects to be explored in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…Forced expression of RECK in cancer cells results in reduced angiogenesis, invasion and metastasis in animal xenograft models (Takahashi et al, 1998;Oh et al, 2001). Mice lacking a functional Reck gene die around embryonic day 10.5 with reduced tissue integrity and defects in various organs, including blood vessels and the central nervous system (Oh et al, 2001;Muraguchi et al, 2007). Studies on RECK gene regulation may therefore yield important insights into the mechanisms of carcinogenesis as well as mammalian development.…”
Section: Introductionmentioning
confidence: 99%
“…RECK was first isolated as a transformation-suppressor gene by cDNA expression cloning (Noda et al, 1989;Takahashi et al, 1998) and found to encode a membraneanchored regulator of several extracellular metalloproteinases, including MMP2, MMP7, MMP9, MT1-MMP, ADAM10 and CD13 (Takahashi et al, 1998;Oh et al, 2001;Miki et al, 2007;Muraguchi et al, 2007;Omura et al, 2009). These proteases have been implicated in tissue remodeling and cleavage of various extracellular molecules under normal and pathological conditions (Sternlicht and Werb, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Reck-deficient mice die around embryonic day 10.5 with reduced tissue integrity (accompanied by dramatic reduction in collagen fibrils), arrested vascular development and precocious neuronal differentiation (Oh et al, 2001;Muraguchi et al, 2007;Chandana et al, 2010). Embryo fibroblasts derived from these mice show unstable focal adhesions, increased speed of migration and reduced directional persistence during migration, and the phenotype can be partially suppressed on fibronectin-coated dishes .…”
Section: Introductionmentioning
confidence: 99%